AKTIVITAS ANTIBAKTERI MINYAK NILAM (Pogostemon cablin) TERHADAP BEBERAPA SPESIES BAKTERI UJI - Retno Widowati; Sri Handayani; Iqba Lasdi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Patchouli (Pogostemon cablin) is a plant that has the potential as a medicinal ingredient. Patchouli contained a lot of essential oils and called patchouli oil. Patchouli oil is commonly used as traditional medicine and aromatherapy. For industries, it is used in the manufacture of pharmaceutical and cosmetic products. Patchouli oil was the result of traditionally distillation of patchouli leaves in Province of Jambi and Aceh. This study aims to determine the antibacterial activity of patchouli oil from Jambi and Aceh, against several pathogenic bacteria. Phytochemical test results showed that the both of patchouli oils contained active compounds, in the form of alkaloids, saponins, phenolics, flavonoids, triterpenoids, and glycosides.The bacteria used in this study were Escherichia coli ATCC 8739, Salmonela typhi ATCC 14028, Staphylococcus aureus ATCC 6539, Staphylococcus epidermidis ATCC 12228, and Pseudomonas aeruginosa ATCC 9027. The methods used in this study were well diffusion and inhibition zones. The results showed that patchouli oil was able to inhibit two of the five bacteria i.e. S. aureus and P. aeruginosa. Jambi patchouli oil was better in inhibiting S. aureus and P. aeruginosa compared to Aceh patchouli oil. The six active compounds in patchouli oil have the potential to inhibit growth or kill bacteria. Key words: Antibacterials, Phytochemical Compounds, Pogostemon cablin, Patchouli Oil